COMPARATIVE ULTRASONOGRAPHIC MEASUREMENT OF RENAL SIZE AND ITS CORRELATION WITH AGE, GENDER, AND BODY MASS INDEX IN NORMAL SUBJECTS IN SULAIMANI REGION - Karim, Shilan Hussein; Mohammed, Naser Abdullah; Aghaways, Ismaeel H.A.; Muhammed, Bryar Ali (European Scientific Journal, ESJ, 2015)
Background: The renal size of a population is a very useful diagnostic parameter in the practice of medicine. Since the renal size is affected by various factors, it is necessary to first determine the normal value. Objective:The aim of this study is to provide an estimation of renal size in normal subjects in Sulaimani Teaching Hospital, and to study its relation with age, gender, and body mass index (BMI) using ultrasonography. Therefore, this provides a standard data for our locality as we are deficient of them. Method:A cross sectional descriptive study was conducted in Sulaimani Teaching Hospital during the period of June 2013 to February 2014. 450 random volunteer person were included in the study aging between 18 - 96 years, without any known renal diseases.The total sample of the study were 450 person. 239 person (53%) were females, while 211 person (47%) were males. The mean of the right renal size in males was 76553.9947 mm3, while the mean of the left renal size was 94493.9mm3. In females, the mean of the right renal size was 68324.0292mm3, while the mean of the left renal size was 84150.43264mm3. Mean renal size for the right kidney was 72210.9842 mm3,While the mean renal size for the left kidney was 89031.0296 mm3. Results:There was a positive correlation between the size of the right and left kidney, with the left kidney size which is larger. There was also a positive correlation between renal size and age, as renal size increased with age till the 5th decade of life. While the male renal size was greater than the female renal size with the same age group, there was a positive correlation between renal size and body mass index (BMI).